Exploring Relationships Among Government Management, Investment, and Sustainable Competitiveness in Indonesia's Maritime Sector - Ahmadi Ahmadi; Didit Herdiawan (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the relationships among government policy, investment, and sustainable competitiveness in Indonesia’s maritime sector, with a particular focus on both direct and mediated effects. Grounded in institutional theory and the Resource-Based View (RBV), the study explains how regulatory frameworks and resource mobilization shape long-term competitiveness outcomes in a developing country context. Methodology: A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to survey data collected from 420 maritime stakeholders, including government agencies, port authorities, shipping companies, investors, and environmental NGOs across key maritime regions. Results: The results demonstrate that government policy significantly influences investment (? = 0.61, p < 0.001) and directly affects sustainable competitiveness (? = 0.34, p < 0.01). Investment also has a strong positive effect on competitiveness (? = 0.47, p < 0.001) and partially mediates the relationship between policy and competitiveness. The model explains substantial variance in investment (65%) and sustainable competitiveness (72%). Conclusion: Government policy plays a dual role as both an investment catalyst and a direct competitiveness driver. Limitations: The study relies on cross-sectional survey data from Indonesia, limiting causal inference and generalizability. Contributions: The findings provide actionable guidance for policymakers in developing countries by demonstrating that regulatory clarity, fiscal incentives, and infrastructure planning must be aligned with targeted investment mechanisms to effectively enhance sustainable competitiveness across economic, environmental, and social dimensions.